Performance of a Pebble Bed Thermal Storage Integrated with Concentrating Parabolic Solar Collector for Cooking - Kedida, Dejene Kebede; Amibe, Demiss Alemu; Birhane, Yilma Tadesse (Journal of Renewable Energy, 2019)
Cooking using biomass, which is commonly practiced in developing countries, causes rampant deforestation and exposure to emission. Hence, utilization of solar energy for cooking is a green solution. As solar radiation is not available at every hour of the day, thermal storage is essential for availing thermal energy at required time of use. Therefore, this work investigates the efficiency of solar cooker with parabolic concentrating collector integrated with thermal storage using 1D finite difference computational model. A cook stove on packed pebble bed thermal storage having 0.3 m diameter and 0.9 m height and a storage capacity of 40.1 MJ of energy during a clear day and 12.85 MJ energy was simulated for charging and discharging (cooking), under Addis Ababa climatic condition for days, with highest and lowest solar irradiance and thermal storage efficiency of 66.7%, cooker thermal efficiency of 45% during discharging of heat by forced convection, and 41% during discharging of heat by conduction, were obtained for the day with the highest solar irradiance. The overall efficiency of the cook stove with thermal storage was 30% and 22% for discharging by forced convection and conduction, respectively. For the day with lowest beam solar irradiance, the storage, thermal and overall efficiencies were 70.9%, 31.1% and 22.0%, respectively. Hence, it can be concluded that solar concentrating cookers with thermal storage can have an overall cooking efficiency between 22% and 30% on a clear sky day when the Sun is overhead in tropical areas.